Success of integrated farming system for enhancing farmer’s income in Mizoram - Kumar, Yengkhom Bijen; Lalramhlimi, B; Lalhruaipuii,; Lalrinsanga, P L; Lungmuana,; Soni, Jeetendra Kumar; Doley, S (Indian Farming, 2023)
The article assesses the impact of integrated farming system (IFS) models against traditional mixed farming system popularly practiced by small farmers. All the four models were found to increase gross income to a range of 115.03–321.69% against traditional mixed farming systems. The best combination of farm components with highest gross income (₹ 1,75,000) and benefit-cost ratio (2.13) was achieved through the integration of Horticulture + Animal Husbandry + Water harvesting. The approach of IFS will not only enhance the income of farmers but also sustain farm productivity as well as improve soil and environmental health. Proper selection offarm components and allocation of farm resources following scientific models would be helpful to farmers to get maximum output from minimum investment and to utilize farm resources efficiently, so that the ultimate goal of improving farmer’s income and enhancing their livelihood would be achieved.